Dampak Tipe Kepribadian, IPK, dan Jenis Kelamin pada Efektivitas Pembelajaran Akuntansi Berbasis Online yang Dimoderasi oleh Kecemasan Berteknologi (Studi Kasus pada Mahasiswa Program Akuntansi Fakultas Ekonomi Unisma dan UIN) - Hermawan, Ismi Istihanah; Diana, Nur; Mawardi, M. Cholid (e_Jurnal Ilmiah Riset Akuntansi, 2023)
The Purpose of this study was to determine the impact of personality, GPA and gender on the effectiveness of online-based accounting learning moderated by technological anxiety. This study uses explanatory research, the method used to analyse is Descriptive Statistical Analysis, Multiple Linear Regression Analysis, Moderation Regression Analysis, Instrument Test, Classical Assumption Test, and Hypothesis Test. The sample of this study were students of the Islamic University of Malang and State Islamic University of Malang majoring in accounting, the sample used was 268 respondents. The results showed that personality type, GPA, and gender had a simultaneous effect on the effectiveness of online-based accounting learning. Personality type and gender have a significant influence with a confidence level of 5% on the effectiveness of online-based accounting learning because they have a tcount > ttable with a significance < 0.05. Meanwhile, GPA has no significant effect on the effectiveness of online-based accounting learning because it has a tcount < ttable with a significance of > 0.05. Keyword : Personality type, GPA, gender, technology anxiety.